Diagnostic performance of a point-of-care high-sensitivity cardiac troponin I assay among Chinese patients with chest pain - Gary Tse; Janet Yuen Ha Wong; Simon Ching Lam; Jonathan Ka Ming Ho; Andy Chun Yin Chong; Calvin Chi Wai Chau; Chi Yip Wong; Johnson Wai Keung Tse; Jeremy Yan Hon Tam (Open Heart)
Background A novel handheld point-of-care high-sensitivity cardiac troponin I analyser has recently been introduced to the market. Evaluating its diagnostic performance against laboratory standards is imperative, given the variations in cardiac troponin levels across populations. This study compared the diagnostic performance between the point-of-care high-sensitivity cardiac troponin I assay (Siemens Healthineers Atellica VTLi) and a laboratory high-sensitivity cardiac troponin I assay (Abbott ARCHITECT STAT High Sensitive Troponin-I) performed using blood samples from various populations (overall, male, female, younger and older) of Chinese patients with chest pain.Methods This cross-sectional study included 585 consecutive Chinese patients (age ≥18 year) who presented to an emergency department with chest pain (lasting >5 min) and were managed following the chest pain protocol between 1 August 2023 and 12 June 2024. For both assays, blood samples were collected at two time points (0 hour (initial) and 3 hour (subsequent)). The primary outcome was the diagnostic performance of the two assays, evaluated with their 99th percentile upper reference limits used as the cut-off values for diagnosing myocardial infarction. The gold standard for comparison was the final diagnoses made by attending physicians.Results The point-of-care and laboratory assays exhibited equivalent sensitivity and negative predictive values (both 100%) for blood samples collected at both time points. However, the point-of-care assay outperformed the laboratory assay in terms of specificity (initial: 90.5% to 96.3% vs 79.8% to 94.7%; subsequent: 87.8% to 94.8% vs 77.7% to 92.4%) and positive predictive value (initial: 24.4% to 30.8% vs 11.6% to 23.5%; subsequent: 12.5% to 25.0% vs 5.9% to 18.8%), particularly in older patients.Conclusion The point-of-care assay is recommended for rapid clinical decision-making. Future studies should explore the effects of its integration into clinical practice and the feasibility of using sex–race–age-specific 99th percentile upper reference limits to enhance its diagnostic performance.